2022
DOI: 10.1017/jns.2022.56
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits are associated with the prevalence of type 2 diabetes: a study among a middle eastern population

Abstract: Worldwide type 2 diabetes (T2D) prevalence is increasing dramatically. The present study aimed to evaluate the association between dietary habits and T2D in an Iranian adult population using a cross-sectional analysis of the Shahedieh cohort study. Participants were adults aged 35–70 years (n 9261) from Zarch and Shahedieh, Yazd, Iran, who attended the baseline phase of the Shahedieh cohort study. Dietary habits including meal frequency, fried-food consumption, adding salt to prepared meals and grilled-food co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(52 reference statements)
1
3
0
Order By: Relevance
“…This aligns with other previous studies [15,16]. Supporting our findings, a study conducted in Iran found an association between fried-food consumption and the risk of type 2 DM [43]. This review found that sweet food consumption was negatively associated with diabetes control, while a plant-based diet reduced triglyceride levels, increased HDL levels, and led to better diabetes management.…”
Section: Discussionsupporting
confidence: 92%
“…This aligns with other previous studies [15,16]. Supporting our findings, a study conducted in Iran found an association between fried-food consumption and the risk of type 2 DM [43]. This review found that sweet food consumption was negatively associated with diabetes control, while a plant-based diet reduced triglyceride levels, increased HDL levels, and led to better diabetes management.…”
Section: Discussionsupporting
confidence: 92%
“…36 In contrast, in a study among the Iranian population, Mahdi et al suggested that no significant association exists between adding salt to prepared meals and the odds of T2DM. 37 Moreover, meta-analysis data from four observational studies showed no association between sodium intake and the prevalence of diabetes. 17 The substantial variance among these studies could be attributed to disparities in study designs, participant demographics, and, most importantly, different measures of salt intake.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Radzeviciene et al reported an approximately 82% heightened risk of T2DM among participants who added salt to prepared meals compared with those who never 36 . In contrast, in a study among the Iranian population, Mahdi et al suggested that no significant association exists between adding salt to prepared meals and the odds of T2DM 37 . Moreover, meta‐analysis data from four observational studies showed no association between sodium intake and the prevalence of diabetes 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another cohort study focused on postmenopausal women found that hazard rates and 95% confidence intervals were 1.38 (1.03, 1.84) for subjects who consumed meals four times per day compared with one to three times per day [ 16 ]. Moreover, a study based on an Iranian population showed that those who have six meals per day are at a higher risk of diabetes than those who eat three meals per day (OR: 2.503, 95% CI: 1.651, 3.793) [ 34 ]. Additionally, there were several studies that also revealed that plenty of health parameters could be improved by reducing energy intake, including glycemic control, β cell function, insulin resistance, lipid profiles, oxidative stress, and inflammation [ 19 , 21 , 24 , 35 ].…”
Section: Discussionmentioning
confidence: 99%